Kontribusi Kawasan Wisata Budaya Dayak Terhadap Tingkat Pendapatan Masyarakat Suku Dayak Kenyah - Mustafa, Putri Rizky Delia; Syarif, Erman; Badwi, Nasiah (UNIVERSITAS NEGERI MAKASSAR, 2020)
Â This study aims to determine the quality of the Dayak cultural tourism area in the village of Pampang village in East Kalimantan and determine the contribution of the Dayak cultural tourism area to the level of income of the Dayak tribe community in the village of Pampang, East Kalimantan. The population in this study were people who work in the Dayak cultural tourism area in the village of Pampang, East Kalimantan as many as 30 people. The number of samples taken was 30 people using total sampling. Retrieval of data in this study using observation techniques, questionnaires, and documentation. Then analyzed using qualitative and quantitative analysis techniques (mix methods). Research data is displayed in the form of frequency and percentage tables. The results showed that the quality of the Dayak cultural tourism area in the village of Pampang was included in the